Digital Transformation Strategy JLU 2030 - (:unkn) unknown; Justus Liebig University Giessen (My University, 2023)
This strategy document formulates the central objectives of Justus Liebig University Giessen in the area of digital transformation up to the year 2030. With the help of subgoals and measurable indicators, these are specified in the activities research, teaching, and IT governance, IT infrastructure, and administration. JLU understands digital transformation as a holistic, comprehensive transformation process. Digital working, teaching, learning, and studying are fully supported with the development and expansion of technical infrastructures and can be used where it makes sense.
Keywords: ddc:000